Jesus – The immigrant Egyptian Jews in Matthew"s Sondergut: A migration perspective - Dube, Zorodzai (HTS teologiese studies, 2019)
Using pull and push factors inspired by the migration theory, this study explains Matthew’s Sondergut concerning Jesus’ flight to Egypt from the perspective of possible pull–push factors associated with Egypt and Palestine during the first century. Within early Christianity, two perception strands concerning Egypt existed: on the one hand, Jews such as Celsus depicted Egypt negatively as a place of magic and oppression. Yet another perspective portrays Egypt as a place of refuge, recuperation and recovery – a view reflected in Luke-Acts, Matthew and some parts of Mark. Not disregarding views that read the story as Midrash or allegory, this study focuses on Matthew’s Sondergut concerning Jesus’ flight to Egypt as narrative explainable from a positive migration perspective, and argues that the prosperity of Egypt and possible political turmoil in Palestine during the first century give plausible reconstruct for Matthew’s Sondergut regarding Jesus’ flight to Egypt as a place of refuge and sustenance.